Development and Simulation of Next Generation SDH Network Management System - Saeed, Bilal; Shahid, Khalil; Khan, Zeeshan (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
In present scenario Network Management System of Next Generation SDH is not performing Offline reporting, offline analysis of alarms, offline performance management and Configurations of network like real time. Any offline configuration of a network when implemented on a real time environment leaves some shortcomings and wrong configuration attributes due to non-availability of Alarms and Performance Management in the presently available offline utility. A simulated platform is developed for implementation of a traffic matrix in an offline environment before implementing over a real time NG SDH Transmission network to reduce the chance of faults or any network disaster.